Is low proteinuria an early predictor of severity of acute pancreatitis?. Issue 11 (November 1989) - Shearman, C P; Gosling, P; Walker, K J
Abstract : Serial six hourly urine collections were made for seven days on 20 patients with acute pancreatitis. Quantitative immunoassay of urinary albumin and IgG on the first urine sample after admission showed increased excretion rates in 14 and 13 patients, respectively. Urinary protein excretion rates remained normal or approached normal by seven days in 17 patients who made uneventful recoveries. The maximum urinary excretion rates of both albumin and IgG within the first 36 hours correlated with the serum C-reactive protein concentration 72 hours after admission. The highest IgG excretion rates were found in three patients who later developed severe complications. These preliminary data suggest that low proteinuria is a very early response in acute pancreatitis, and that it may reflect the severity of inflammation.